2022
DOI: 10.1002/jgm.3418
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0008717 promotes renal cell carcinoma progression by upregulating FBXO17 via targeting miR‐217

Abstract: Background Renal cell carcinoma (RCC) is a common lethal urological malignancy. Circular RNAs are assumed to play important roles in cancer development. The objective of the present study was to investigate the role and action mechanism of circ_0008717 in RCC. Methods The expression of circ_0008717, miR‐217 and F‐box protein 17 (FBXO17) mRNA was detected by a real‐time quantitative polymerase chain reaction. Cell proliferation was examined using a cell counting kit‐8 assay and an 5‐ethynyl‐2′‐deoxyuridine assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…circRNA influences the transcription, protein stability and enzyme activity of key enzymes and transporters of RCC glycolysis by regulating downstream target genes, and participates in glucose metabolism. CircME1 and circ_0008717 promote glycolysis in clear cell RCC [ 21 , 22 ]. This study discovered a new circRNA (hsa_circ_0003596, circCOL5A).…”
Section: Discussionmentioning
confidence: 99%
“…circRNA influences the transcription, protein stability and enzyme activity of key enzymes and transporters of RCC glycolysis by regulating downstream target genes, and participates in glucose metabolism. CircME1 and circ_0008717 promote glycolysis in clear cell RCC [ 21 , 22 ]. This study discovered a new circRNA (hsa_circ_0003596, circCOL5A).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hsa-miR-153-3p may be involved in the development of diabetic nephropathy [ 57 ]. miR-217 is associated with a variety of kidney diseases, such as tubular fibrosis [ 58 ] and renal cell carcinoma [ 59 ]. The MALAT1/miR-145/focal adhesion kinase (FAK) pathway was also confirmed to play an important role in TGF-β1-induced renal fibrosis [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that circ_0008717 and lung metastasis are independent prognostic factors through Cox multivariate regression analysis. After knocking down the expression of circ_0008717, the proliferation, migration and invasion of tumor cells can be reduced, and apoptosis can be promoted ( Shen et al, 2022 ). circ_0081001 was another potential biomarker of OS prognosis, which was selected from chemotherapy and chemotherapy-sensitive OS cell lines, showing high levels in advanced OS, chemotherapy-resistant and lung metastasis ( Wei et al, 2021 ) ( Figures 2 , 3 ).…”
Section: Prognostic Biomarkersmentioning
confidence: 99%